One-year surveillance of body mass index and cardiorespiratory fitness in UK primary school children in North West England and the impact of school deprivation level. Issue 10 (31st January 2019) - Mann, Steven; Wade, Matthew; Jones, Michelle; Sandercock, Gavin; Beedie, Chris; Steele, James
Abstract : Objectives: Cardiorespiratory fitness (CRF) is independently associated with health and academic attainment in childhood and adolescence. Yet overweight/obesity remains the focus in public health policy. Surveillance of body mass index (BMI) and CRF considering school deprivation levels is limited. Therefore, we examined this in English primary schools. Methods: Participants (n=409) were students (9–10 years) from 13 schools. BMI and CRF (20 m shuttle run) were measured at three time points across the academic year and a fourth after summer recess. Results: BMI z-scores significantly decreased (p=0.015) from autumn (z=0.336 (95% CI 0.212 to 0.460)) to spring (z=0.252 (95% CI 0.132 to 0.371)), and then significantly increased (p=0.010) to summer (z=0.327 (95% CI 0.207 to 0.447)). CRF significantly increased (p<0.001) from autumn (z=0.091 (95% CI −0.014 to 0.196)) to spring (z=0.492 (95% CI 0.367 to 0.616)), no change (p=0.308) into summer (z=0.411 (95% CI 0.294 to 0.528)) and a significant decrease (p<0.001) into the following autumn term (z=0.125 (95% CI 0.021 to 0.230)). BMI was unaffected by deprivation; however, pupils from the most deprived areas saw significantly greater reductions in CRF compared with pupils from affluent areas. No time, or deprivation level, by sex interactions were found. Conclusion: Significant reductions in children's CRF occurred over the summer recess and were greater among children from schools in the most deprived areas. This may help inform future research into interventions targeting physical activity of schoolchildren, particularly over the summer recess.